FIB 4 Score (Liver Fibrosis) and Attending Level of Vitamin D in Chronic Hepatitis C Patients: FIB 4 Score (Liver Fibrosis) - Sami, Tariq; Kammeruddin, Karim; Imran, Muhammad; Ali, Mahboob; Rahman, Nadia; Waheed, Syed Abdul; Ali, Javed; Bibi, Afsha; Latif, Abdul; Mazher, Saeed (Pakistan Journal of Health Sciences, 2023)
Millions of people around the world are affected by chronic hepatitis C (HCV), which is a global health issue. It is a major contributor to chronic liver conditions such as cirrhosis, hepatocellular carcinoma, and liver fibrosis. For optimal therapy and intervention, prompt identification of liver fibrosis is essential. The rate of hepatic fibrosis progression in HCV-infected patients varies substantially. Objective: To evaluate the vitamin D level and liver fibrosis degree by non-invasive Fib 4 score among chronic hepatitis patients. Methods: This Cross-sectional study was conducted at a tertiary care hospital in Karachi, Pakistan, from August 2020 to September 2022. 65 participants were recruited through a non-probability sampling technique. Results: Study findings show that 21.9% of the patients have low risk for advanced fibrosis, whereas 9.2% have an Intermediate risk for advanced fibrosis, and 69.2% have a high risk for advanced fibrosis. Moreover, findings also revealed that among 65 patients, 66.2% have a deficient amount of Vitamin D, whereas 16.9% have an insufficient amount of Vitamin D level and 16.9% have a sufficient amount of vitamin D. Furthermore, the findings also showed significant association based on p-value (0.001) between Age and Fib4 score of the participant. Conclusions: In conclusion, the study revealed that a significant proportion of chronic hepatitis C patients were at high risk for advanced fibrosis, while vitamin D deficiency/ insufficiency were prevalent among the majority of the patients.